2006
DOI: 10.1097/01.fpc.0000197465.14340.d4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hyperbilirubinaemia and UDP-glucuronosyltransferase 1A1 (UGT1A1) polymorphism in adult HIV-infected Thai patients treated with indinavir

Abstract: In contrast to Caucasian HIV-infected patients treated with indinavir, the promoter polymorphism (UGT1A1*28) is of less significance than the coding region (UGT1A1*6) mutation as a risk factor for hyperbilirubinaemia. The Ki values determined for indinavir inhibition of UGT1A1 are consistent with an interaction in vivo, with an additive effect in patients with already impaired bilirubin glucuronidation activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…The potent inhibition of UGT2B10 by several drugs observed in this study is consistent with previous reports from this laboratory, demonstrating that inhibition of other UGT enzymes (e.g., UGT 1A1, 1A9, 2B4, and 2B7) may potentially precipitate DDIs and drugendobiotic interactions (Boyd et al, 2006;Uchaipichat et al, 2006b;Miners et al, 2010b;Raungrut et al, 2010;Pattanawongsa et al, 2015). These observations reinforce the recent recommendations of Regulatory Agencies that new drugs should be evaluated for their potential to inhibit UGT enzymes.…”
Section: Discussionsupporting
confidence: 81%
“…The potent inhibition of UGT2B10 by several drugs observed in this study is consistent with previous reports from this laboratory, demonstrating that inhibition of other UGT enzymes (e.g., UGT 1A1, 1A9, 2B4, and 2B7) may potentially precipitate DDIs and drugendobiotic interactions (Boyd et al, 2006;Uchaipichat et al, 2006b;Miners et al, 2010b;Raungrut et al, 2010;Pattanawongsa et al, 2015). These observations reinforce the recent recommendations of Regulatory Agencies that new drugs should be evaluated for their potential to inhibit UGT enzymes.…”
Section: Discussionsupporting
confidence: 81%
“…22 However, the K I reported for fluconazole using zidovudine as a substrate is 529 mM. 22 Consistent with this report, no inhibition was seen below 500 mM with any of the isozymes (Fig. 3G).…”
Section: Resultssupporting
confidence: 79%
“…The antifungal fluconazole (Diflucan, Pfizer, Inc., New York, NY) was included in this screen because it was reported to be a selective inhibitor of UGT2B7. 22 However, the K I reported for fluconazole using zidovudine as a substrate is 529 mM. 22 Consistent with this report, no inhibition was seen below 500 mM with any of the isozymes (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Huang et al (2005) reported that 15% of patients homozygous for the wild-type allele versus 90% of patients homozygous for the UGT1A1*28 allele developed hyperbilirubinemia. Bilirubin plasma levels and the number of cases of jaundice were higher in the group of patients carrying the two mutant alleles (Zucker et al, 2001;Rotger et al, 2005b;Boyd et al, 2006;Rodrí-guez-Nóvoa et al, 2007). Rodríguez -Nóvoa et al (2006) confirmed the relationship between the UGT1A1*28 genotype and the risk of hyperbilirubinemia with atazanavir and indinavir.…”
Section: Pharmacokinetics Of Udp-glucuronosyltransferase and The Riskmentioning
confidence: 99%